2013
DOI: 10.1590/s1516-35982013001100004
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and performance of sheep fed cactus pear in substitution of corn

Abstract: -The objective of this study was to evaluate the feeding behavior and performance of Santa Ines sheep subjected to different levels of substitution of corn by cactus pear in the diet. Forty-five non-castrated male Santa Inês sheep with initial live weight of 27.50±0.48 kg were distributed in a completely randomized design with five treatments (0, 70, 140, 210 and 280 g/kg DM) and nine replicates. Dry matter and neutral detergent fiber intakes showed quadratic behavior. Times spent eating, ruminating and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…The average TDN content in our study was 67.56% (Table 3). This is comparable to the reported 69.3% TDN content in cactus pear silage [45,55], 61% in cactus cladodes and 70.87% in O. ficusindica [56]. Ref.…”
Section: Fiber Contentssupporting
confidence: 88%
“…The average TDN content in our study was 67.56% (Table 3). This is comparable to the reported 69.3% TDN content in cactus pear silage [45,55], 61% in cactus cladodes and 70.87% in O. ficusindica [56]. Ref.…”
Section: Fiber Contentssupporting
confidence: 88%
“…Moreover, PPCP also has several biological activities, including anti-hyperlipidemic, hypercholesterolemic, anti-inflammatory, antimicrobial, and antiviral actions [24]. Commonly, the PPCP has been used as a dietary alternative feedstuff for animal feeds, including the partial replacement of grains such as corn [25,26] or barley [18]. However, the knowledge regarding the use of PPCP as a potential feed supplement in small ruminant diets due to its high content of phytochemicals is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In general, cactus is characterized by a low CP concentration. Average values of 39 g/kg and 58 g/kg have been reported by Costa et al (2013) and Abidi et al (2009), respectively. However, higher CP values were reported by Batista et al (2003 a , b) (60–77 g/kg) for several cactus cultivars from north-eastern Brazil, and Ayadi et al (2009) showed CP concentration of 88 g/kg in cladodes of Tunisian O. ficus indica .…”
Section: Discussionmentioning
confidence: 70%
“…This characteristic of low NDF and ADF concentrations is associated with high non-structural carbohydrate concentration, making the spineless cactus a valuable source of fermentable carbohydrates for ruminants. On average, cactus TC concentration ranged from 62 to 84 g/kg DM, while NFC range from 31 to 58 g/kg DM (Tegegne et al , 2007; Costa et al , 2013; Tosto et al , 2015). Results from the current study were within these ranges.…”
Section: Discussionmentioning
confidence: 99%